Leverage competencies : the key to financial leadership success - Militello, Frederick C. (Financial Times Prentice Hall books., 2002)
In today's integrated and complex financial world, financial leaders can't succeed on financial skills alone. Today's most successful companies have discovered that ""leveraged competencies""--Often referred to as ""soft"" or ""leadership"" skills -- are crucial to the success of financial leaders. Drawing upon research at eight outstanding global companies, this book provides a complete blueprint for enterprises who want tomorrow's leaders to have all the skills they need to win -- financial and leadership. This book focuses on the emotional competencies and leadership skills executives nee